(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: Describe the knowledge, attitude and correct practice on prevention of Hand, Foot and Mouth disease of mothers with children under 5 years old studying at Kindergarten in Vinh Phong Commune, Vinh Thuan District. Methodology: A cross-sectional descriptive study using quantitative research methods, handing out self-filling forms Kindergarten Vinh Phong commune, Vinh Thuan district in 2022 Results: General characteristics of mothers in the study: The mean age was 28.05 ± 5.2 years, the age group 22-35 years accounted for 55.1%. There are 58.7% mothers of children with high school education and 23.9% mothers with college education or higher. Employees work and democracy, self-employment accounts for a high percentage (72.4%). 94.9% of mothers had access to information about limb disease, mainly through mass media such as radio, newspaper, television, internet (63.8%). The percentage of mothers with correct knowledge is 33.3%; has true mode is 67.4% and the performance is 18.1%. The percentage of mothers who are correct in all 3 areas is 13%. Conclusion: The percentage of mothers with correct knowledge is 33.3%; has true mode is 67.4% and the performance is 18.1%. The percentage of mothers who are correct in all 3 areas is 13%.